NAFTA Students'Whistle-blowing Perceptions: A Case of Sexual Harassment (La percepción advertidora de Ios alumnos en TLC: un caso de acoso sexual - Peek, L.; Roxas, M.; Peek, G.; Robichaud, Y.; Covarrubias, B.; Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración U.A.N.L., 2005)
Abstract, Whistle-blowing mechanisms in the U.S. have gained more prominence as an element of legal compliance and antifraud programs. Sexual harassment is asignificant business risk in terms of financial costs and the loss of reputation. lt is important for corporations to develop sexual harassment policies and to provide mechanisms for employees toreport sexual harassment behaviors to upper level management. This paper reports on business students' responses to a possible Sexual Harassment scenario from Arthur Andersen's Business Ethics Program and the actions that the characters in the video should take in terms of whistle-blowing. l fall 2004,78 students from two U.S. universities and one Mexican and one Canadian university participated in the project as part of the NAFIA Challenges of Accounting and Busrness Sysfems Granf funded by the United States Department of Education Fund for the lmprovement of PostSecondary Education (FIPSE), Human Resources Development Canada (HRDC), and Mexico's Secretaría de Educación Pública (SEP). Students from the three NAFTA countries were shown the vignette and asked to respond to a pre-questionnaire concerning the characters' behaviors and possible actions. The students were then asked to discuss the situation and write a report from the ooints of view of the three characters in the vignette and also to find a copy of an organizations' sexual harassment policy from the Internet. At the end of the project the students responded to a postquestionnaire. The students were asked to consider whether the characters should report the possible harasser iotheir supervisor, end thus engage in whistle-blowing behavior. Hypoiheses are formulated for the three NAFTA countries based on Hofstede's cultural dimensions and comparisons are made based on overall responses to the pre-and posfquestionnaire. There were significant differences, but in some cases not in the direction expected. Gender differences are also explored, but there were few significant differences. The authors are working under the NAFTA Challenges of Accounting and Busrness Sysfems Grant from the United States Depaftment of Education Fund for the lmprovement of PosfSecondary Education (FIPSE), Human Resources Development Canada (HRDC), and Mexico's Secretaría de Educación Pública (SEP).